Application of Telemedicine for Preliminary Screening of Autism Spectrum Disorder - Qiu, Ting; Zhang, Heng; Zhou, Conghua; Tang, Qilong; Wang, Lizhen; Ke, Xiaoyan (Frontiers in Pediatrics, 2022)
Objective: Preliminary screening for autism spectrum disorder (ASD) is mainly performed offline in China. This method is time consuming, labor intensive, inefficient and costly. These complications limit its routine implementation in some hospitals and child health institutions, especially community health service centers. Thus, the present study explored the clinical applicability of an online screening system for ASD detection based on telemedicine technology. Methods: The online screening system designed based on the WeChat platform and section A of the Chinese-validated version of the checklist for autism in toddlers (CHAT-23-A) and combined with an independent Research and Development (R&D) program. The sensitivity and specificity were 0.92 and 0.90, respectively, and the area under the receiver operating characteristic curve (AUC) values for all 23 items and 7 key items were 0.934 and 0.91, respectively. Results: The online screening system based on telemedicine technology was not limited by time, space, region, or medical resources and showed high sensitivity, specificity, and diagnostic efficiency for ASD. Conclusion: The online screening system based on telemedicine technology is suitable for large-scale population ASD screening in childcare institutions.